The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.4102/hsag.v25i0.1460
|View full text |Cite
|
Sign up to set email alerts
|

Work-related musculoskeletal disorders amongst undergraduate nursing students at the University of Johannesburg

Abstract: Background:Work-related musculoskeletal disorders (WRMSDs) present as pain or discomfort in the musculoskeletal system that individuals experience from work-related activities. Substantial research evidence exists on qualified nurses with WRMSDs, but there is a distinct lack of research regarding nursing students and their work environment in South Africa.Aim: The primary aim of this study was to establish a baseline prevalence of musculoskeletal disorders (MSDs) amongst undergraduate nursing students. The sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…The total score is then expressed as a percentage, with higher scores indicating greater disability. Disability levels were categorized as minor (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), modest (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), severe (25-34), and complete (35-50). The Oswestry Disability Index (ODI) has demonstrated good test-retest reliability, with an Intraclass Correlation Coefficient (ICC) ranging from 0.72 to 0.98, and a Cronbach's alpha value of 0.89, reflecting excellent internal consistency (10,11).…”
Section: Methodsmentioning
confidence: 99%
“…The total score is then expressed as a percentage, with higher scores indicating greater disability. Disability levels were categorized as minor (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), modest (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), severe (25-34), and complete (35-50). The Oswestry Disability Index (ODI) has demonstrated good test-retest reliability, with an Intraclass Correlation Coefficient (ICC) ranging from 0.72 to 0.98, and a Cronbach's alpha value of 0.89, reflecting excellent internal consistency (10,11).…”
Section: Methodsmentioning
confidence: 99%
“…The prolonged and repetitive use of mobile phones, coupled with inadequate ergonomics, can potentially lead to muscular and joint problems among nursing students. These issues could be manifested as neck pain, discomfort in the shoulders, upper back pain, and issues in the hands or wrists [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the constant completion of strenuous tasks throughout the day, it is not uncommon for healthcare workers to experience musculoskeletal injuries. The most frequent of these injuries are in the upper and lower back, the neck, and the shoulders [ 1 ]. These injuries are a direct result of poor posture and repetitive tasks in awkward positions [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent of these injuries are in the upper and lower back, the neck, and the shoulders [ 1 ]. These injuries are a direct result of poor posture and repetitive tasks in awkward positions [ 1 ]. In 2018, a small survey of healthcare workers, including registered nurses and nursing assistants, reported that over 23,000 days were missed from work that year.…”
Section: Introductionmentioning
confidence: 99%